Development of stem-collaborative learning based arithmetic teaching material for enhancing students' critical thinking - Nikmah, Nafidatun; Musbikhin; Mandala, Arif Sapta (Pusat Studi Pengembangan Pembelajaran Matematika, 2024)
The online learning methods used during the pandemic have impacted students' ability to communicate, collaborate, and build interpersonal relationships, which are crucial for developing collaborative skills. Students face limitations in receiving feedback and direct guidance from classmates and teachers, which affect the development of their collaborative skills. This research aims to develop STEM-Collaborative based teaching materials for arithmetic learning that can enhance students' critical thinking abilities. Research and development (R&D) approach was employed in this study using the 4-D development model. The development stages involved identification, design, and development. The research population consisted of 10th-grade students in a Vocational High School in the Bondowoso region. The research sample was selected using cluster random sampling technique, including individual trials, small group trials, and field test. Data was collected through expert validation sheets, questionnaires, and students' critical thinking ability tests. The research produced products in the form of Student Worksheets, Lesson Plans, and STEM-Collaborative Learning-based Assessment of Critical Thinking. The results showed that the developed instructional materials were valid based on expert evaluations. According to student assessments, the developed instructional materials were highly practical with a score percentage of 86%. The test results demonstrated a high improvement in students' critical thinking (n-gain = 0,703). There was a significant difference in students' critical thinking abilities between the experimental group and the control group (p < 0,05). Therefore, the developed instructional materials can be considered effective in fostering students' critical thinking. The implementation of STEM-Collaborative learning from these teaching materials has provided a positive contribution to enhancing students' critical thinking skills.